2023
DOI: 10.3390/ijms24054309
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Epithelial Cells Shape Immune Responses through the Modulation of Inflammasomes and Lipid Metabolism

Abstract: Lacrimal gland inflammation triggers dry eye disease through impaired tear secretion by the epithelium. As aberrant inflammasome activation occurs in autoimmune disorders including Sjögren’s syndrome, we analyzed the inflammasome pathway during acute and chronic inflammation and investigated its potential regulators. Bacterial infection was mimicked by the intraglandular injection of lipopolysaccharide (LPS) and nigericin, known to activate the NLRP3 inflammasome. Acute injury of the lacrimal gland was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Consistent with the previous notion that the LG is a part of the mucosal immune barrier system [54,105,106], our study revealed a substantial presence of resident immune cells from both the lymphoid and myeloid lineages in the gland. We recently showed that the epithelial LG cells are sentinel cells that can sense danger signals/tissue damage and recruit immune cells by activating the inflammasome pathway [107]. Therefore, it is not surprising to find a considerable number of innate immune cells and resident regulatory T cells in the LG in homeostatic conditions, as they can rapidly initiate an inflammatory response upon sensing alarm signals.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous notion that the LG is a part of the mucosal immune barrier system [54,105,106], our study revealed a substantial presence of resident immune cells from both the lymphoid and myeloid lineages in the gland. We recently showed that the epithelial LG cells are sentinel cells that can sense danger signals/tissue damage and recruit immune cells by activating the inflammasome pathway [107]. Therefore, it is not surprising to find a considerable number of innate immune cells and resident regulatory T cells in the LG in homeostatic conditions, as they can rapidly initiate an inflammatory response upon sensing alarm signals.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-then induces the production of more alarmins in the extracellular environment by salivary gland epithelial cells, creating a damaging autoinflammatory loop that promotes local and systemic damage and results in the continuation of the disease. 39,40 with functional tests. The application of various imaging modalities in the evaluation of SS lacrimal gland lesions is detailed below.…”
Section: The Pathology Of the Lacrimal Gland In Ssmentioning
confidence: 99%
“…Following their activation, plasmacytoid dendritic cells release large amounts of IFN‐α and B‐cell activating factor (BAFF), which aid in the proliferation of B cells inside the germinal center. IFN‐ then induces the production of more alarmins in the extracellular environment by salivary gland epithelial cells, creating a damaging autoinflammatory loop that promotes local and systemic damage and results in the continuation of the disease 39,40 …”
Section: Introductionmentioning
confidence: 99%